2013
DOI: 10.3126/ije.v2i1.9224
|View full text |Cite
|
Sign up to set email alerts
|

Status Of Endemic Plants Of Bangladesh And Conservation Management Strategies

Abstract: The present study was aimed at recognizing the status of 28 endemic plants of Bangladesh and determining their conservation management strategies. These endemics belong to 17 angiosperm families and constitute about 0.78% of the total species of the country. Of these endemics, 2 species were least concern, 10 rare and 7 endangered, and need to give immediate conservation priority. Another 9 endemics were assessed to be extinct since no report of collection for more than 100 years was available and could not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…(2013) recognized 28 endemic plant species' conservation status through their own field research, whether or not it is obvious that the IUCN standard approach was followed. Rahman and Rashid (2013) noted that 11 of the 25 endemic plants (Pasha 2011) and 7 of the 8 endemic plants ( Khan et al 2001) are found outside of Bangladesh. We discovered that 7 plants on Rahman and Rashid's (2013) list are present globally (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2013) recognized 28 endemic plant species' conservation status through their own field research, whether or not it is obvious that the IUCN standard approach was followed. Rahman and Rashid (2013) noted that 11 of the 25 endemic plants (Pasha 2011) and 7 of the 8 endemic plants ( Khan et al 2001) are found outside of Bangladesh. We discovered that 7 plants on Rahman and Rashid's (2013) list are present globally (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the concept of endemism requires familiarity with the geographic range of a species. Until it is found again in another country or region, a newly discovered species is often only found in a small area and is assumed to be endemic to that location (Rahman and Rashid, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of microorganisms was influenced by soil depths. Rahman and Rashid (2013) examined the status of 28 endemic plants of Bangladesh and determined their conservation management strategies. This study revealed that 10 endemics are categorized as extinct since no reports of second collection have been made after type collections for more than 100 years.…”
Section: 'This Journal Provides Immediate Open Access To Its Contentsmentioning
confidence: 99%
“…,Tutul et al (2010),Arefin et al (2011),Rahman et al (2010Rahman et al ( , 2012Rahman et al ( , 2013,Rahman et al (2010a),Uddin et al (2013),Rashid and Chowdhury (2013),Uddin et al (2015),Arefin et al (2017) have been consulted to trace the report of collection/occurrence of the Lamiaceous taxa of Bangladesh. In the result the following Latin words e.g.…”
mentioning
confidence: 99%